The Impact of Financial Technology on MSME Financial Performance: The Mediating Role of Payment Transaction Convenience in Seberang Ulu - Tur Wasiah, Alima; Sartika, Dewi (Yayasan Sinergi Kawula Muda, 2025)
This study examines the impact of financial technology on the financial performance of micro, small, and medium enterprises (MSMEs), with payment transaction convenience as a mediating variable. Data were collected from 100 MSME participants in the Seberang Ulu region who actively use financial technology services. A quantitative approach with non-probability sampling was applied, and the data were analyzed using structural equation modeling–partial least squares (SEM-PLS) with SmartPLS 4. The findings show that financial technology positively and significantly influences both MSME financial performance and payment transaction convenience. Moreover, payment transaction convenience partially mediates the relationship between financial technology and financial performance. These results suggest that fintech adoption improves MSME productivity, streamlines transactions, and enhances financial management. The study recommends that MSME operators strengthen fintech adoption to optimize operations, while policymakers and institutions support this process through training and literacy programs that foster sustainable competitiveness.